Analysis of the corn market in Mexico from a price perspective - Reyes Santiago, Ester; Bautista Mayorga, Fidel; García Salazar, José Alberto (Acta Universitaria, 2022)
Corn is the most important basic grain in Mexico; despite this, large quantities are imported to satisfy consumption. The present article aimed to determine the factors that affect the behavior of the corn grain market in Mexico, to estimate the effect of the guaranteed price on the supply, and to analyze the effect of the import price on this market.A model of simultaneous equations was formulated using annual data from the corn market from 1999 to 2020, the model was estimated by least squares in two stages (LS2E). The results indicate that increasing the guaranteed price by 37.4% causes production to grow by 8.38%, and the effects of increasing the import price by 20% causes production to increase 2.1% and consumption to decrease 5%. Synergize with other support programs for Mexican agriculture is recommended to further increase production and thus advance on self-sufficiency.